2021
DOI: 10.3390/s21134411
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Image Metric of Periodic Structures in an Opto-Digital Angle Measurement System

Abstract: Measurement of the object angular position and its change is one of the important tasks in measurement technique. Our method is based on determination of the angular position of a 2D periodical optical pattern (2D mark) at the object, captured by the sensor of a digital camera. System performance can be frustrated by errors in determination of the spot coordinates on the camera sensor; by the presence of lens aberrations; by deviations from the parallelism of the pattern planes and the camera sensor; and by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the work [19], which was already mentioned above, among other important results on correcting distortions of the mark image in a real measuring system, an estimate of the manufacturing error of the mark photomask was obtained. It is shown that the error of deviation of the coordinates of the mark elements from the calculated values has a distribution close to normal with RMS of about 1 micron.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work [19], which was already mentioned above, among other important results on correcting distortions of the mark image in a real measuring system, an estimate of the manufacturing error of the mark photomask was obtained. It is shown that the error of deviation of the coordinates of the mark elements from the calculated values has a distribution close to normal with RMS of about 1 micron.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The paper also presented experiments with the implementation of the mark on a digital screen (a standard smartphone), significantly expanding the understanding of the possibilities of such measuring procedures. A separate study [19] was devoted to correction of distortions in the brand image to minimize the Δs parameter in formula (1), including correction of the tilt of the mark image, correction of lens distortion, correction of mark manufacturing errors. That corrections reduce the value of Δs by an order of magnitude (from tenths to hundredths of a pixel).…”
Section: Using a Two-dimensional Scale For Angular Measurementsmentioning
confidence: 99%